Konsep Connectivity dalam Redesain Interior GECO Creative Digital Hub Surabaya - Lavenia Emilia Inneke; Laksmi Kusuma Wardani; David Tan Kayogi (Intra, 2019)
Creative Digital Hub is a term that describes a place that accommodates creative activities in working in the digital field. The main targets of space users are young people consisting of those in the Y, Z, A generation in the future (young entrepreneurs, startup workers, students and students). With the development of technology that continues to increase, the digital generation in Surabaya needs a space that can facilitate creation in the digital field. The design using design thinking methods includes the stages of observing the needs and activities of space users, field surveys, analyzing survey results by producing programming products, brainstorming producing a concept that is applied in design schematics and study models, to produce final products: layouts, floor plans and ceilings, perspective, presentation model, and others. The designed room facilities are lobby, private space, meeting room, public work area, work studio, pantry, event space / classroom and service area.